2021
DOI: 10.1002/solr.202100459
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Properties and Structure of Boron–Hydrogen Complexes in Crystalline Silicon

Abstract: The subject of hydrogen–boron interactions in crystalline silicon is revisited with reference to light and elevated temperature‐induced degradation (LeTID) in boron‐doped solar silicon. Ab initio modeling of structure, binding energy, and electronic properties of complexes incorporating a substitutional boron and one or two hydrogen atoms is performed. From the calculations, it is confirmed that a BH pair is electrically inert. It is found that boron can bind two H atoms. The resulting BH2 complex is a donor w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 53 publications
(120 reference statements)
2
19
0
Order By: Relevance
“…[45] for a recent review). Based on junction spectroscopy and first-principles calculations, the relocation of hydrogen and the formation of a boron-dihydride complex (BH 2 ) in p-type Si has been proposed as a possible culprit for LeTID [46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[45] for a recent review). Based on junction spectroscopy and first-principles calculations, the relocation of hydrogen and the formation of a boron-dihydride complex (BH 2 ) in p-type Si has been proposed as a possible culprit for LeTID [46].…”
Section: Introductionmentioning
confidence: 99%
“…Based on junction spectroscopy and first-principles calculations, the relocation of hydrogen and the formation of a boron-dihydride complex (BH 2 ) in p-type Si has been proposed as a possible culprit for LeTID. [46] The understanding of LeTID is strongly tied with our knowledge regarding the issues discussed above. They involve processes driven by kinetics and excitations (quenching, illumination, annealing), all of which cannot be understood if we leave vibrational and electronic excitations out of the physical picture.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing the electron affinity of B s O 2 –H structures with the same quantity for a 512‐atom pristine supercell, we have found that the false(/0false) transition level of B s O 2 –H resides above the conduction band minimum for both A and A′ configurations. Hence, as in the reaction between B and H, [ 25 ] the acceptor level of B s O 2 is removed from the gap as a result of its connection to H. No donor transitions were found either.…”
Section: Resultsmentioning
confidence: 99%
“…Reactions identified in the table as (1)–(3) were already studied in ref. [25]. They show that the binding energy of a bond‐centered proton (ground state of hydrogen in p‐type Si) to normalBnormals is 0.73 eV.…”
Section: Resultsmentioning
confidence: 99%
“…Another possibility is a single kind of passivating ions, H + (1), but with a compensation by hydrogen‐related donors H 2 B [ 26 ] —positive species that are formed by trapping H + by HB (and thus composed of B − and two H + ). This version was also tried; it can roughly fit the hole profile in Figure 3b but fails to fit the hydrogen profile in Figure 2a.…”
Section: Hydrogen Concentration Profiles In Passivated Samplesmentioning
confidence: 99%